Towards virtual dataspaces for material scientific data cloud. (2nd January 2013) - Liu, Zhenyu; Hu, Jingyuan; Li, Yang; Huang, Yi
Summary: New challenges for large‐scale data management and sharing have arisen because of the information evolution from massive data to "big data". In this paper, we propose the concept of virtual dataspaces and domain scientific data cloud (DSDC) to address the challenges of management, reusability, and service of scientific data in scientific domain. The application of DSDC is also introduced, which is used in the materials science domain for e‐Science applications. Virtual dataspaces is then defined, which is used to integrate and organize both structured and unstructured scientific data in cloud environment. To build the virtual dataspaces, a logical resources model based on ontology is discussed. And then a new mapping and evolutionary model of virtual dataspaces is described in a "pay‐as‐you‐go" fashion. As such, we introduce a "semi‐automatic evolution" method. A scientific data cloud application model is also proposed for defining service template. Finally, the virtual dataspaces and DSDC are verified by "material service safety evaluation", and the results show that our approach is efficient in scientific data management and suitable for data‐intensive application. Copyright © 2013 John Wiley & Sons, Ltd.